National and EU budget expenditures supporting the organisation of the fruit and vegetable market in Poland after 2010 = Krajowy i unijny budżet rolny Polski po 2010 r. redukcja wydatków i kierunki zmian - Bieniek-Majka, Maryla; Czyżewski, Andrzej; Matuszczak, Anna (Zielona Góra: Faculty of Economics and Management Press)
The aim of the article is to discuss the role of national and EU budget resources supporting organisation in the fruit and vegetable market. By way of introduction, the level and dynamics of (national and EU) budget expenditures supporting the agricultural sector in general was presented. Next, expenditures on the support for the fruit and vegetable market were analysed in detail.
Keywords: wydatki budżetu państwa; wydatki UE; zmniejszenie wydatków; rynek owoców i warzyw; national budget expenditure; EU expenditure; expenditure reduction; fruit and vegetable market